2019
DOI: 10.1021/acssensors.9b00224
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic Detection of Superoxide Using Oxoporphyrinogen and Porphyrin

Abstract: The superoxide (O 2 •−) ion is a highly reactive oxygen species involved in many diseases, hence its non-invasive detection is desirable to identify the onset of pathological processes. Here, we employed photoacoustic (PA) spectroscopy, which enables imaging at ultrasound resolution with sensitivity of optical modality, for the first time to detect O 2 •− , using stimuliresponsive contrast agents. Meso (3, 5-di-tert-butyl 4-hydroxyphenyl) porphyrins and oxoporphyrinogens were used as PA contrast agents, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The OxP exhibited completely different optical properties and reactivity than porphyrins. The pristine OxP did not exhibit a NIR-absorption (λ = 654 nm); however, upon capturing the O 2 − , the absorption maximum was redshifted by up to 240 nm and showed an over 10-fold increase in the PA signal (along with the increase in molar absorption coefficient) [86]. Among the variety of ROS and reactive nitrogen species (RNS) explored in vitro, PAI studies showed high selectivity and maximum signal gain for O 2 − (Figure 7c).…”
Section: Core-modified Tetrapyrroles As Pa Probesmentioning
confidence: 97%
“…The OxP exhibited completely different optical properties and reactivity than porphyrins. The pristine OxP did not exhibit a NIR-absorption (λ = 654 nm); however, upon capturing the O 2 − , the absorption maximum was redshifted by up to 240 nm and showed an over 10-fold increase in the PA signal (along with the increase in molar absorption coefficient) [86]. Among the variety of ROS and reactive nitrogen species (RNS) explored in vitro, PAI studies showed high selectivity and maximum signal gain for O 2 − (Figure 7c).…”
Section: Core-modified Tetrapyrroles As Pa Probesmentioning
confidence: 97%
“…7a ). 96 The complexation of the probes and O 2 ˙ − or F − would cause an enhancement in the PA signal, accompanied by a red-shift in the spectrum. Unlike the probes containing cleavable groups, which exhibit continuous consumption of the substrates, these probes were almost time-independent.…”
Section: Activatable Photoacoustic Probesmentioning
confidence: 99%
“…[7][8][9][10] However, most tetrapyrrolic PA systems are limited to the NIR region. 7,11 Absorption greater than 1000 nm, termed the second near-infrared region (NIR-II: 1000-1350 nm), allows for deeper tissue penetration and reduced light scattering than the NIR-I region (700−950 nm). [12][13][14][15][16] Current NIR-II PA contrast agents comprise organic semiconducting conjugated polymers; very few are solely organic-based.…”
Section: Introductionmentioning
confidence: 99%